A Scream in Occupied Cairo: Muhammad Jibril’s Muhammad Jalas - Hüseyin Yazıcı (Şarkiyat Mecmuası)
Muhammad Jibril began to use his name in Arab literature, particularly in Egyptian literature, in the last quarter of the 20th century. He can be described as a prominent figure who left his mark on the city of Alexandria, writing significant works in both the novel and short story genres. In some of his writings, he symbolizes the Jewish involvement in contemporary issues such as the Israeli-Palestinian conflict and the Israeli-Arab dispute, consistently siding with the Palestinians. He even depicts Israel as a state that tries convincing others of the lies it has fabricated. The story of “The Jewish Neighborhood” toucheson a sensitive subject and describes the struggle of Muhammad Jalas, who represents the resistance of an occupied community against the injustices caused by the Jewish community in occupied Cairo. This study briefly examines the historical context of Jews in Egypt and other periods are briefly examined, alongside the role of the British, who protected the Jews during the occupation of Cairo. This provides a foundational foundation for story analysis. The tensions between the minority and majority populations in occupied Cairo are also considered. The primary source for this study is Jibril’s collection titled “Jewish Neighborhood,” particularly focusing on the eponymous story. Naturally, a sense of anxiety and hopelessness has always dominated the human experience of being caught between East and West. In the story we analyze, the society witnessed an impressive story of resistance in the midst of a long period of despair and frustration between the Jews and the helpless Egyptian government.